Estudos eletroquímicos de complexos de Cu(II) de antibióticos da classe das fluorquinolonas - Pedro Henrique Moreno de Souza (2011)
The fluoroquinolones represent an important class of synthetic compounds that have been studied because of its chelating capacity and their applications as antibacterial agents. Recent studies for the blood trypomastigotes of T. cruzi have shown promising results for analysis of trypanocidal activity in vitro metal complexes with ligands fluoroquinolones. Knowing that the mechanisms of action of anti-Tcruzi may involve redox reaction, this work has used the technique of cyclic voltammetry to study the electrochemical behavior of complex [CuCl2(SPAR)].2H2O (1) and its analogue [CuCl2(SPAR)(fen)].3H2O (2), where SPAR is the ligand of the family of fluoroquinolones sparfloxacin and fen is 1,10- phenanthroline. The voltammetric studies for both the complex (1), And for the complex (2) were performed in aqueous solution (KCl - 1.0 mol L-1) at different pH using glassy carbon working electrode.At physiological pH, the cyclic voltammograms of the complex (1) at different scan rates (n), had two pairs of redox peaks of quasi-irreversible nature, attributed the species Cu2+/Cu+ and Cu+/ Cuo. The mechanism diagnosed at pH 7.4 consists of two consecutive oneelectron-transfer steps (EE mechanism). For complex (1) it has been observed a dependence of the reduction process of Cu2+ species to Cu+ at different pH values, and could be obtained by cyclic voltammetry, the pKa value equal to 6.10. The electrochemical behavior of complex (2) at physiological pH, was different from the complex (1). For complex (2), cyclic voltammograms showed only one pair of redox peaks attributed to species Cu2+/Cu+. At pH 7.4, the electrochemical process was proved ndependent, showing a quasi-reversible nature of the high values of n and characterized by irreversible disproportionation reaction following a reversible electron transfer (ErCi - disproportionation mechanism) to low values of n. We also observed that the redox reactions attributed to the pair Cu2+/ Cu+ are favored with a possible change of mechanism at pH values above 4.0